Assisted Gestation and Transgender Women. (17th December 2014) - Murphy, Timothy F.
Abstract Developments in uterus transplant put assisted gestation within meaningful range of clinical success for women with uterine infertility who want to gestate children. Should this kind of transplantation prove routine and effective for those women, would there be any morally significant reason why men or transgender women should not be eligible for the same opportunity for gestation? Getting to the point of safe and effective uterus transplantation for those parties would require a focused line of research, over and above the study of uterus transplantation for non‐transgender women. Some commentators object to the idea that the state has any duty to sponsor research of this kind. They would limit all publicly‐funded fertility research to sex‐typical ways of having children, which they construe as the basis of reproductive rights. This objection has no force against privately‐funded research, of course, and in any case not all social expenditures are responses to 'rights' properly speaking. Another possible objection raised against gestation by transgender women is that it could alter the social meaning of sexed bodies. This line of argument fails, however, to substantiate a meaningful objection to gestation by transgender women because social meanings of sexed bodies do not remain constant and because the change in this case would not elicit social effects significant enough to justify closing off gestation to transgender women as a class.